Effectiveness of Cutting Speed ​​of SS 316 L Material on Surface Roughness in Laser Cutting Process - Sigit Arrohman; Andri Sulistyo; Catur Harsito (Jurnal Ilmiah Dinamika Rekayasa, 2025)
Cutting metal materials using Laser Cutting can determine the quality of the cutting material. This is because laser cutting uses high speed, so it can improve the quality of the cut material. SS316 L metal is a metal used in the manufacturing industry. The choice of SS 316 L metal aims to prevent corrosion, have high strength and be easy to maintain. The aim of this research is to determine the cutting speed parameters in laser cutting using SS 316 L material. The method used is by varying the cutting speed of the laser machine with speeds of 60 mm/minute, 70 mm/minute, 80 mm/minute, 90 mm/minute, 100 mm/min. Observation of surface roughness tests with two variations vertically and horizontally. Test samples three times for each test object. The results of this research were that the lowest (smooth) surface roughness was obtained with a cutting speed variation of 100 mm/minute and the highest (coarse) at a cutting speed of 60 mm/minute for both vertical and horizontal sampling variations. So, the faster the cutting speed of the laser machine can reduce the roughness of the SS 316 L metal surface.